ANALISIS MENULIS UNSUR SERAPAN OLEH MAHASISWA PGSD SEMESTER IV KELAS II - Adelina Ginting (PGSD Universitas Negeri Medan, 2018)
This study aims to describe the ability of students in writing the element of absorption with the right (good and right). This research was conducted on PGSD student of Semester IV Class II of academic year 2015/2016 as research subject, the number of students of PGSD Semester IV class II is 29 people. The research was conducted by giving a questionnaire as a source of what will be analyzed. Questionnaires to be done by students only write B (true) and S (wrong). Based on the results of the survey, 48.27% (14 students) were categorized good, 24.13% (7 students) were sufficient kateogri, and 27.58% (8 students) were categorized as unfavorable.Keywords: absorption element, foreign language, and Indonesian language.